The effect of transfer pricing and foreign ownership on tax avoidance in consumer non-cyclicals sector companies - Siti Najmi Choiria; Agus Puji Priyono (Educoretax, 2026)
This study is motivated by the widespread practice of transfer pricing and the high level of foreign ownership among companies in the consumer non-cyclicals sector, which are suspected of being used to minimize corporate tax burdens. This study aims to examine the effect of transfer pricing and foreign ownership on tax avoidance, both partially and simultaneously, in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This study applies a quantitative approach using a sample of 25 companies selected through purposive sampling, resulting in 75 observations over three years. Secondary data were obtained from the companies' audited annual financial statements published on the Indonesia Stock Exchange and were analyzed using multiple linear regression with IBM SPSS Statistics. Grounded in agency theory, the results show that transfer pricing and foreign ownership have a positive and significant effect on tax avoidance, both partially and simultaneously, with an adjusted coefficient of determination of 63.3 percent. These findings are expected to serve as an evaluation for companies to improve transparency in related-party transactions, for tax authorities to strengthen supervision of multinational entities, and as a reference for further research to consider other relevant determinants of tax avoidance. Keywords: Transfer Pricing; Foreign Ownership; Tax Avoidance; Agency Theory